Expression and prognostic significance of APAF-1, caspase-8 and caspase-9 in stage II/III colon carcinoma: caspase-8 and caspase-9 is associated with poor prognosis - Sträter, Jörn; Herter, Ines; Merkel, Gaby; Hinz, Ulf; Weitz, Jürgen; Möller, Peter (International journal of cancer, 2010)
Apoptosis protease activating factor-1 (APAF-1), caspase-8 and caspase-9 are important factors in the execution of death signals. To study their prognostic influence in colon carcinoma, expression of APAF-1, caspase-8 and caspase-9 was determined by immunohistochemistry in normal colon mucosa (n = 8) and R0-resected stage II/III colon carcinomas (n ≥ 124) using a semiquantitative score. Staining results were correlated with disease-free survival by Kaplan-Meier estimates, and multivariate Cox analyses were performed. In normal colon, APAF-1 and caspase-8 are most strongly expressed in the luminal surface epithelium, whereas caspase-9 is expressed all along the crypt axis. In colon carcinomas, there is considerable variability in the expression of these proapoptotic factors, although complete loss of caspase-8 and caspase-9 is rare. APAF-1 expression did not correlate with disease-free survival. Instead, both expression of caspase-9 and high-level expression of caspase-8 in a majority of tumor cells were significantly associated with adverse prognosis (p = 0.004 and p = 0.029, respectively). The influence of caspase-8 expression was mainly seen in patients with stage III colon carcinoma (p = 0.011), whereas the prognostic influence of caspase-9 expression was significant in stage II cases (p = 0.037) and just failed to be significant in stage III tumors (p = 0.0581). After adjusting for confounding factors in a multivariate Cox analysis, the effect of caspase-9 in predicting disease-free survival was confirmed (p = 0.003). Our data suggest that, in colon carcinomas, expression of caspase-8 and caspase-9 is significantly associated with poor survival. Caspase-9 may be an independent prognosticator in colon carcinoma.
Erstmals am 09 December 2009 online veröffentlicht
Gesehen am 28.08.2023